TOWARDS PRONATALISM – BALTIC FAMILY POLICY IN EUROPEAN COMPARISON IN 2002 AND 2010 - Ainsaar, Mare; Riisalu, Helina (Baltic Journal of Political Science, 2015)
The majority of comparative analyses of family policy have been oriented towards western European countries and only very few have included Baltic and eastern European countries. The aim of this paper is to analyse family policy in Baltic countries in European comparison about ten years after regaining independence, in 2002, and in 2010. Family policy is divided into two categories for analysis: 1) support for families from around the birth of a child until the first birthday of the child, pronatalist policies; and 2) child well-being policies, support for the family when the child is older. All policy data are standardised according to the relative wealth in the particular country. Results demonstrate that after ten years of country specific family policy processes, Lithuania developed a very specific pronatalist family policy type compared with Estonia and Latvia. In 2010, Estonia and Latvia also obtained a more pronatalist approach, but the Baltic countries did not belong to any one particular crystallised family policy group.